Primary sclerosing cholangitis associated with CREST (calcinosis, Raynaud phenomenon, oesophageal dysmotility, sclerodactyly and telangiectasia) in an elderly woman: a case report. (December 2015) - Powell, Alice; McNeil, Julian
Abstract Introduction CREST (calcinosis, Raynaud phenomenon, oesophageal dysmotility, sclerodactyly, and telangiectasia) syndrome comprising calcinosis cutis, Raynaud phenomenon, esophageal dysmotility, sclerodactyly and telangiectasia and primary sclerosing cholangitis are both chronic fibrotic diseases but the association between them is extremely rare. While primary sclerosing cholangitis has been associated with diffuse cutaneous scleroderma, the association with limited cutaneous scleroderma or CREST has not been previously reported in the literature. This case report illustrates the association between CREST and primary sclerosing cholangitis. Case presentation We report the case of an 84-year-old Asian woman with a long history of CREST who was admitted with abdominal pain, fatigue and progressive derangement of her liver enzymes. This was initially thought to be secondary to her bosentan therapy for pulmonary hypertension but it persisted despite bosentan being ceased. Primary sclerosing cholangitis was subsequently diagnosed on magnetic resonance cholangiopancreatography and she was referred to a hepatologist for treatment. Conclusions This case highlights the need to consider primary sclerosing cholangitis in patients with CREST who present with abdominal symptoms and deranged liver enzymes when other causes have been excluded. Relevant differential diagnoses for this presentation, which can be difficult to exclude, include immunoglobulin G4-associated cholangitis and antimitochondrial antibody negative primary biliary cirrhosis. It is of particular significance to rheumatologists and gastroenterologists but has broader relevance to all medical specialists involved in the care of patients with CREST.